How to Make Students Happy During Periods of Online Learning: The Effect of Playfulness on University Students’ Study Outcomes - Li, Yuqian; Hu, Fengfei; He, Xiao (Frontiers in Psychology, 2021)
University students’ study outcomes, their psychological wellbeing in particular, have been considered closely by both education researchers and practitioners. It is worth exploring ways to improve the quality of life of students, especially during the pandemic period when millions of students around the world have taken online courses at home. This paper tests the influence of playfulness on the levels of life satisfaction and school burnout of college students. To examine our hypotheses, we distributed our survey to 353 Chinese university students (mean age 20.10 years) in their online learning semester in 2020 due to the outbreak of COVID-19. Correlation analysis and path analysis were applied to analyze the data. The results show that playfulness positively relates to life satisfaction and negatively correlates to school burnout. Moreover, a sense of control mediates these relationships. Both theoretical and practical implications are discussed.